Teaching and Learning In, With and For Community: Towards a pedagogy for education for sustainable development - Lorna Down (Environmental Association of Southern Africa, 2010)
The paper explores how one teaches and learns for sustainable development primarily through analysing education for sustainable development (ESD) initiatives in the Caribbean within the framework of service learning. The paper proposes that a pedagogy for ESD will require positioning education in the centre of community. What that means in terms of content and methodology is the focus of our discussion.